Twenty Years Working with Neighbours. Citizen Participation, Is It Possible? What We Have Learned in 20 Years - Remesar, Antoni (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2019)
In 1999, the Governing Council of the Universitat de Barcelona approved the creation of the POLIS Research Center. Later, in 2016, the Center was ratified after passing an assessment of the Catalan Accreditation Agency (AGAUR). The Centre has an interdisciplinary vocation and brings together researchers from different research groups at the University of Barcelona and cooperates with nine European and Ibero-American universities in the fields of Arts, Architecture and Human and Social Sciences. Academically, the Centre has promoted the doctoral program Public Space and Urban Regeneration (1998–2017) and the Master’s Degree in Urban Design: Art, City, Society (since 2007) and the publication of the journal On the w@terfront. The research object of the Centre is the city and its public space and, more specifically, the role of citizens in the production of Public Art and Urban Design. For this reason, the work of the Centre covers the topics related to Urban Regeneration, Sustainability, Urban Governance, Civic Remembrance, Heritage. Throughout its twenty-year history, the Centre has developed a series of projects for citizen participation in various areas of the periphery of Barcelona: River Besòs (municipality of Sant Adrià de Besòs) La Mina neighbourhood (municipality of Sant Adrià de Besòs) and the Barcelona’s neighbourhoods of Baró de Viver and Bon Pastor. A characteristic of the work of the centre has been, and is, the endorsement of citizen participation, through an innovative approach based on enabling the creative empowerment of the neighbours within the framework of Participatory Action Research. This approach is based on a project methodology, as it is understood in various project disciplines from Art to Architecture, from Design to Engineering. This article, associated with the itinerant exhibition “20 years working with neighbours,” reviews the founding project carried out by the Centre, “Social Uses of the River Besòs” (1997–1999), analysing the lessons learned, with the aim of clarifying the research criteria that the Centre follows for the development of citizen participation projects.